(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Background: Lung cancer is the leading cause of cancer deaths worldwide. Lung cancer is often insidious, producing no symptoms until the disease is well advanced. In approximately 7-10% of cases, lung cancer is diagnosed in asymptomatic patients. Some patients are asymptomatic for skeletal metastasis and a recent prospective study showed that in staging of non-small cell lung cancer (NSCLC), failure to perform a bone scan could miss asymptomatic bone metastasis in 14–22% of patients. Radionuclide bone scintigraphy with 99m Tc MDP (Technetium-99mmethylene diphosphonate) is very useful nuclear imaging tool to detect skeletal metastasis with a sensitivity of 98.2% and a specificity of 95.2%. The aim of this study was to detect the asymptomatic skeletal metastasis of non-small cell lung cancer patients by 99mTc MDP bone scan. Patients and methods: It is a retrospective study, carried out from January 2015 to December 2016 in Institute of Nuclear Medicine and Allied Sciences, Rajshahi. Bone scan was performed by an intravenous bolus injection of 20 m Ci 99mTc MDP. Bone phase images were taken at three hours after injection of the radiotracer. Results: A total of 52 patients were enrolled in the study. The mean age of the patients was 57.6 ± 14.5 years (mean ± SD) with range from 36 to 75 years and 42 (80.77%) were male and 10 (19.23%) were female. Out of 52 patients, only 06 (11.54%) patients were diagnosed as positive and 46 (88.46%) were negative for bone metastasis. Out of 06 patients with positive skeletal metastasis 04 (66.67%) patients had multiple sites (two or more) and 02 (33.33%) patients had solitary site of bone involvement. Common sites of metastasis were in thoracic (83.33%) and lumbar spine (83.33%), ribs (50%), pelvic bones (33.33%), long bones (16.66%), skull (16.66%) and other bony sites including clavicle, sternum, scapula, sacrum (16.66%). Regarding staging prior to bone scan, out of 06 bone scan positive patients 03 (50%) patients were in stage III, 02 (33.33%) patients were in stage IV and 01(16.67%) patient was in stage II. On the basis of histopathology, out of 06 skeletal metastatic patients 04 (66.67%) patients had adenocarcinoma, 01 (16.67%) patient had squamous cell carcinoma and 01 (16.67%) had large cell carcinoma. The exclusion of bone metastasis is important in the initial staging of non-small cell lung cancer. Conclusion: There is debate about whether bone scans should be performed routinely or restricted to patients who present with clinical or laboratory indicators suggesting skeletal metastasis. The present study indicates that if bone scans were done only in patients reporting skeletal symptoms an important number of patients (11.54%) would have been miss-staged due to asymptomatic bone metastasis. As bone scan is very cost effective in comparison to other imaging modalities (MRI / PET-CT), it can play a vital role in detecting asymptomatic skeletal metastasis in NSCLC patients. Bangladesh J. Nuclear Med. 20(2): 110-114, July 2017